(untitled) (AYUSHDHARA, 2017)
The body is consisting of Dosha, Dhatu and Mala. Mala in terms of Mutra, Purish and Sweda are the waste products of Anna rasa. In any pathological condition the characters of Dosha, Dhatu and Mala gets altered. Among these factors, clinical examinations of Mutra and Purish have been described in Ayurveda. The methods of examination of stool have not been elaborately mentioned in ancient text of Ayurveda. In modern era, there is an urgent need to evolve a comprehensive method of stool examination as per modern parameters in accordance with principles of Ayurveda, so that this can be followed by the bedside of patients on clinical practice as well as in pathological laboratory. This is consisting collection of stool sample, examination and interpretation of the findings. Stool can be examined macroscopically on the basis of following parameters: colour, odour, consistency, presence of mucus, presence of blood, and presence of any special characters. Each of the parameters can be further interpreted on the basis of different clinical features of stool mentioned under Purvarupa, Rupa, Asadhyalaksna of different disease. This comprehensive approach towards stool examination will not only validate Ayurvedic principles on the basis of modern knowledge, this will also help in diagnosis, prognosis and treatment of diseases as well as will be very useful to make differential diagnosis of a disease.